An Investigation into the Influence of 360-Degree Performance Evaluation on Job Performance: Crafting a Conceptual Framework - Uma Raman.M, Anand.J, G.Gokul Kumari, Lama Sameer Khoshaim, Sager Alharthi, Shweta Sharma (Journal of Informatics Education and Research, 2024)
Recent studies underscore the significance of employee performance appraisal within the realm of strategic human resources management, highlighting the influence of organizational context. This paper proposes a conceptual framework for employee performance appraisal that integrates contextual factors, emphasizing the critical role of strategic human resources management. The model encompasses two sets of fundamental performance criteria: procedural and representative, along with a novel category of profile performance criteria. These form the basis for developing adaptable, customized, and meaningful employee performance appraisal systems and processes aimed at enhancing both individual and organizational performance.To remain competitive in today's constantly evolving industry, businesses must maintain their adaptability. Continuous data collection and analysis are essential for making informed decisions and taking appropriate actions. Since the early 20th century, managers' primary interests have been linked to the success of their companies. This systematic review aimed to evaluate the most effective methodologies for measuring employee performance in organizations. Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique, researchers conducted a comprehensive review of the literature, focusing on articles, research papers, and other relevant materials related to key approaches for staff performance measurement and their associated factors.The systematic review findings indicated that collaboration initiatives had positive and statistically significant effects on employee performance. Performance measurement efforts aim to identify employees' strengths and weaknesses and to motivate them to enhance their performance. Employee performance measurement demonstrates a positive relationship between performance evaluation and employee motivation. Performance evaluation systems should be designed to consider the perspectives of other team members and align with the worker’s own goals.